PENGARUH KEPERCAYAAN TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR(OCB) DENGAN NARSISME SEBAGAI VARIABEL MODERASI PADA UMKM KOTA BENGKULU - Febzi Fiona; Indah Oktari Wijayanti (Unib Press Universitas Bengkulu, 2020)
Abstract. HRM have a role as a thinker, planner, and controller especially in term of Organizational Behaviour. Organizational Citizenship Behavior (OCB) is positive concept which covers an intentions and outcomes, when these behavior have positively effect for organization. Many factors can influence OCB and one of them is trust. The purpose of this study is to examine the effect of trust on OCB and to see the role of narcissism as a moderating variable. The population of this study was all UMKM in Bengkulu city. All data with 80 people were obtained from UMKM Diskopukm Bengkulu City. Sampling collection have been collected using probability random sampling and the data using SPSS as the tool of analyzation. The results of the study were concluded that Trust had a significant positive effect on OCB in UMKM employees in Bengkulu city and narcissism have negatively impact to trust in UMKM employees in Bengkulu city. Keywords:Trust; Organizational Citizenship Behaviour; Narcissism.